Designing Automatic Meter Reading System Using Open Source Hardware and Software - Dragan Mlakić; Srete Nikolovski; Emir Alibašić (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The importance of quality of the measured values is very dependent on the device that measures these values: the size of the sample, the time of measurement, periods of measurement, the mobility and the robustness of the device, etc. Contemporary devices intended for the measurement of physical quantities that are on the market vary in price, as well as and the quality of the measured values. The rule "the more expensive the better" is not necessarily always a rule that is valid because it all depends on the characteristics and capabilities of the device, and the customer’s needs. In this paper, a device based on "Open Source" components of hardware and software will be presented. Device was used to measure voltages and currents on low voltage networks, on which a virtually unlimited number of sensors can be added, and the device is assembled of components available on electronic components Internet.